Fish sperm cryopreservation using biodegradable containers: New low-cost and environment-friendly methodology - de Souza França, Thales; Gomes, Itamar Cossina; Sanches, Eduardo Antônio [UNESP]; Atehortúa, Maritza Pérez; dos Santos Teixeira, Nathalia; Rodrigues, Rômulo Batista; de Freitas, Thaiza Rodrigues; Benato, Jhony Lisbôa; Marques, Lis Santos; de Souza, Ana Regina Seabra [UNESP]; Streit, Danilo Pedro (Oxford University Press (OUP), 2023)
Containers used to cryopreserve sperm are made with non-biodegradable plastic compounds, having a high monetary and environmental cost. Therefore, the development of biodegradable alternative containers for cell cryopreservation is necessary. Thus, this study aimed to evaluate the efficiency of hard-gelatin and hard-hydroxypropyl methylcellulose (HPMC) capsules as low-cost and biodegradable alternative containers for sperm cryopreservation. Sperm from 12South American silver catfish Rhamdia quelen were individually cryopreserved in plastic straws 0.25 mL (as control), hard-gelatin, and hard-HPMC capsules. The quality of post-thaw sperm cryopreserved in the different containers was checked by measuring spermatozoa membrane integrity, kinetic parameters, mitochondrial activity, fertilization, hatching, and normal larvae rates. The samples cryopreserved in straws showed a higher percentage of membrane integrity (68%) than those frozen in hard-gelatin (40%) and hard-HPMC capsules (40%). However, we did not observe differences between the samples stored in straws and hard capsules for the rest of the tested sperm parameters. Thus, based on the high sperm fertility capability, both capsules were efficient as cryopreservation containers for maintaining sperm functionality.